The design of a self-tuning controller (STC) based on pole placement / Sheilani Shaari - Shaari, Sheilani (1999)
The design of a self-tuning controller (STC) based on pole placement is proposed in this paper. The slowly varying process parameters are identified using the recursive lease squares estimation method. The objective is to change the controller setting based on the system parameters that have been estimated when changes occur in the systems. Many techniques can be applied in the controller design. However, in this paper the pole placement method is utilised. The analysis of the controller is done through simulation using MATLAB. However in the design of the estimator, QBasic was used. It is shown the pole-zero controller gives good response. Similarly, the recursive least squares estimator provides a reasonable estimates of the systems parameters.